Optical properties of ytterbium ion doped phosphate glass prepared by sol-gel method [electronic resource] - Noor Azwen Noor Azmy, 1987- (2012)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2012